Trends in Incidence of Methicillin-resistant Staphylococcus aureus Bloodstream Infections Differ by Strain Type and Healthcare Exposure, United States, 2005–2013. (25th February 2019) - See, Isaac; Mu, Yi; Albrecht, Valerie; Karlsson, Maria; Dumyati, Ghinwa; Hardy, Dwight J; Koeck, Mackenzie; Lynfield, Ruth; Nadle, Joelle; Ray, Susan M; Schaffner, William; Kallen, Alexander J
Abstract: Background: Previous reports suggested that US methicillin-resistant Staphylococcus aureus (MRSA) strain epidemiology has changed since the rise of USA300 MRSA. We describe invasive MRSA trends by strain type. Methods: Data came from 5 Centers for Disease Control and Prevention Emerging Infections Program sites conducting population-based surveillance and collecting isolates for invasive MRSA (ie, from normally sterile body sites), 2005–2013. MRSA bloodstream infection (BSI) incidence per 100 000 population was stratified by strain type and epidemiologic classification of healthcare exposures. Invasive USA100 vs USA300 case characteristics from 2013 were compared through logistic regression. Results: From 2005 to 2013, USA100 incidence decreased most notably for hospital-onset (6.1 vs 0.9/100 000 persons, P < .0001) and healthcare-associated, community-onset (10.7 vs 4.9/100 000 persons, P < .0001) BSIs. USA300 incidence for hospital-onset BSIs also decreased (1.5 vs 0.6/100 000 persons, P < .0001). However, USA300 incidence did not significantly change for healthcare-associated, community-onset (3.9 vs 3.3/100 000 persons, P = .05) or community-associated BSIs (2.5 vs 2.4/100 000 persons, P = .19). Invasive MRSA was less likely to be USA300 in patients who were older (adjusted odds ratio [aOR], 0.97 per year [95% confidence interval CI, .96–.98]), previously hospitalized (aOR, 0.36 [95% CI, .24–.54]), or had central lines (aOR, 0.44 [95% CI, .27–.74]), and associated with USA300 in people who inject drugs (aOR, 4.58 [95% CI, 1.16–17.95]). Conclusions: Most of the decline in MRSA BSIs was from decreases in USA100 BSI incidence. Prevention of USA300 MRSA BSIs in the community will be needed to further reduce burden from MRSA BSIs. Abstract : Population-based incidence for methicillin-resistant Staphylococcus aureus (MRSA) bloodstream infections by strain type was calculated from data across selected counties in 5 US states. USA100 MRSA incidence declined in all epidemiologic categories, but USA300 MRSA incidence only declined for hospital-onset infections.